Measuring website service quality for Malaysian companies / Voon Boo Ho, Karen Kueh and Mohd Zawawi Mohd Zafian - Voon, Boo Ho; Kueh, Karen Meng Koon; Mohd Zafian, Mohd Zawawi (Research Management Institute (RMI), 2009)
A customer-perceived quality service has been widely used towards enhancing the customers’ satisfaction and loyalty. The same situation is also applicable for the online services; in an increased use of websites as a channel for information presentation and provision of other services. Hence, the website service quality perceptions of users need to be understood so as to be managed more effectively. The key dimension of this study is to identify the website service quality through the qualitative and quantitative approaches. The website quality theories, focus groups and survey results generate numerous dimensions and items for the understanding and measuring the website service quality of various public-listed companies in Malaysia, particularly from the users’ viewpoint. The laboratory-based method obtains data from the external users’ websites whereas mail surveys aims to gather the views from the organizations’ website. These two approaches use to obtain the perceptual data for further quantitative analysis. Based on the Reliability and Factor Analysis as well as Structural Equation Modeling, there are six valid and reliable dimensions of website service quality identified, namely: Assurance, Tangibles, Content Quality, Technical Quality, Organisation Information, and Address. The implications and future research directions will be also discussed in the following sections of this study.